2006
DOI: 10.1097/00002820-200605000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Follow-up After Treatment for Lung Cancer

Abstract: Pressure on lung cancer clinics is increasing with the "2-week wait" initiative. This initiative is one of the key targets set out in the National Health Service (NHS) Cancer Plan for the United Kingdom, whereby all patients presenting with symptoms which may be indicative of a cancer diagnosis will be seen by a consultant within 2 weeks of initial presentation at their primary care provider. This has resulted in busy clinics, with the potential for extended clinic waiting times and unmet needs for information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 22 publications
3
77
0
1
Order By: Relevance
“…In addition, it is clear that groups of health professionals, including GPs and specialist nurses, are willing, with certain caveats, to assume greater responsibility for the routine follow-up of patients with cancer (Grunfeld et al, 1995;Papagrigoriadis and Heyman, 2001;Moses et al, 2004;Cox et al, 2006). Our results seem to strengthen these findings, as they support the notion that GP-led follow-up would be attractive to a large proportion of individuals with melanoma, and their GPs.…”
Section: Comparison With Other Researchsupporting
confidence: 73%
“…In addition, it is clear that groups of health professionals, including GPs and specialist nurses, are willing, with certain caveats, to assume greater responsibility for the routine follow-up of patients with cancer (Grunfeld et al, 1995;Papagrigoriadis and Heyman, 2001;Moses et al, 2004;Cox et al, 2006). Our results seem to strengthen these findings, as they support the notion that GP-led follow-up would be attractive to a large proportion of individuals with melanoma, and their GPs.…”
Section: Comparison With Other Researchsupporting
confidence: 73%
“…The perceived benefit of this is to facilitate diagnosis of recurrent disease, monitor the effectiveness and side-effects of treatment, manage comorbidity, and identify and treat psychosocial problems. [1][2][3][4] There is also evidence that patients value the psychological and social support that cancer follow-up provides, [5][6][7][8] and find it reassuring. [9][10][11] Conversely, hospital follow-up might also prompt unnecessary tests, raise anxiety, provide false reassurance, and delay the patient's return to full function.…”
Section: Introductionmentioning
confidence: 99%
“…However, discussions considering service redesign should primarily focus on improving the quality of service provision and the potential of nurses to enhance aspects of patient care. The acceptability of nurse led follow up has been demonstrated in a range of cancer sites including lung (Moore et al 2002;Cox et al 2006b), breast (Koinberg et al 2004), and prostate cancer (Faithfull et al 2001;Booker et al 2004). A qualitative breast cancer study of patient perceptions of routine follow up care (Pennery and Mallet 2000) reported that 54% of women questioned would prefer their follow up care to be provided by the nurse specialist as they were more 'supportive' and had the necessary 'time, skills and knowledge'.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the majority of patients (79%) reported feeling uncomfortable raising psychological and emotional concerns at their clinic appointment as they were conscious of taking up too much time. Nurse led follow up provides an opportunity for patients to discuss emotional and psychological concerns (Cox et al 2006b), and for nurses to utilise their specialist skills in providing holistic care.…”
Section: Introductionmentioning
confidence: 99%